Research Progress on the Mechanism of Milk Fat Synthesis in Cows and the Effect of Conjugated Linoleic Acid on Milk Fat Metabolism and Its Underlying Mechanism: A Review - Yuanyin Guo; Ziang Wei; Yi Zhang; Jie Cao (Animals, 2024)
Milk fat synthesis in cows mainly includes the synthesis of short- and medium-chain fatty acids, the uptake, transport, and activation of long-chain fatty acids (LCFAs), the synthesis of triglycerides, and the synthesis of the genes, transcription factors, and signaling pathways involved. Although the various stages of milk fat synthesis have been outlined in previous research, only partial processes have been revealed. CLA consists of an aggregation of positional and geometric isomers of linoleic fatty acid, and the accumulated evidence suggests that the two isomers of the active forms of CLA (cis-9, trans-11 conjugated linoleic acid and trans-10, cis-12 conjugated linoleic acid, abbreviated as c9, t11-CLA and t10, c12-CLA) can reduce the fat content in milk by regulating lipogenesis, fatty acid (FA) uptake, oxidation, and fat synthesis. However, the mechanism through which CLA inhibits milk fat synthesis is unique, with most studies focusing only on the effects of CLA on one of the genes, transcription factors, or signaling pathways involved. In this study, we summarized the structure and function of classic genes and pathways (mTOR, SREBP, AMPK, and PPARG) and new genes or pathways (THRSP, METTL3, ELOVL, and LPIN1) involved in each stage of milk fat synthesis and demonstrated the interactions between genes and pathways. We also examined the effects of other substances (melanin, nicotinic acid, SA, etc.). Furthermore, we evaluated the influence of β-sitosterol, sodium butyrate, Met arginine, and Camellia oleifera Abel on milk fat synthesis to improve the mechanism of milk fat synthesis in cows and provide a mechanistic reference for the use of CLA in inhibiting milk fat biosynthesis.